1998
DOI: 10.1002/(sici)1097-4652(199810)177:1<174::aid-jcp18>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cellular tryptophan metabolism in human fibroblasts by transforming growth factor-β: Selective inhibition of indoleamine 2,3-dioxygenase and tryptophanyl-tRNA synthetase gene expression

Abstract: Alterations in the rate of cellular tryptophan metabolism are involved in mediating important biological activities associated with cytokines and growth factors. Indoleamine 2,3-dioxygenase (IDO) and tryptophanyl-tRNA synthetase are enzymes of tryptophan metabolism whose expression in a variety of cells and tissues is highly inducible by interferon-gamma (IFN-gamma). Transforming growth factor-beta (TGF-beta) antagonizes many cellular responses to IFN-gamma. The interaction of these two cytokines plays an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 60 publications
7
30
0
Order By: Relevance
“…As expected from other studies on myeloid cells, IFN-γ induced the expression of IDO mRNA ( Figure 1A). In the presence of IFN-γ, TGF-β decreased and TNF-α increased IDO expression (data not shown), consistent with others' results (Kwidzinski et al 2005;MacKenzie et al 1999;Robinson et al 2003;Yuan et al 1998). However IL-4, which has been reported to inhibit IDO expression in a number of cell types, increased IFN-γ induced IDO expression ( Figure 1B).…”
Section: Il-4 Increases Ifn-γ Induced Ido Expression In Microgliasupporting
confidence: 91%
See 3 more Smart Citations
“…As expected from other studies on myeloid cells, IFN-γ induced the expression of IDO mRNA ( Figure 1A). In the presence of IFN-γ, TGF-β decreased and TNF-α increased IDO expression (data not shown), consistent with others' results (Kwidzinski et al 2005;MacKenzie et al 1999;Robinson et al 2003;Yuan et al 1998). However IL-4, which has been reported to inhibit IDO expression in a number of cell types, increased IFN-γ induced IDO expression ( Figure 1B).…”
Section: Il-4 Increases Ifn-γ Induced Ido Expression In Microgliasupporting
confidence: 91%
“…The results from the present study in mouse microglia are consistent with previous reports showing that the expression of IDO and WRS is upregulated by IFN-γ. However, many have reported that IL-4 and IL-13 antagonize the effects of IFN-γ (Chaves et al 2001;Doherty et al 1993;Musso et al 1994;O'Keefe et al 1999;Oswald et al 1992;Yuan et al 1998). In distinct contrast, here we show for the first time that in microglia, IL-4 and IL-13 modulate the expression of these enzymes in a distinct fashion (summarized in Figure 9A, B).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Selective serotonin reuptake inhibitors (SSRI) have been reported to improve depression in advanced cancer (Holland et al, 1998), and in melanoma treated with interferon a (Musselman et al, 2001) since the latter also upregulates IDO (Taylor and Feng, 1991). However, these SSRI antidepressant effects might not depend on IDO-mediated serum tryptophan reduction, and studies of the effect of IDO inhibitors (Yuan et al, 1998) on cancer-related QoL deterioration would be needed to confirm the mechanism suggested by the present findings.…”
Section: Discussionmentioning
confidence: 61%